TRAF6 promotes osteogenesis in ADSCs through Raf-Erk-Merk-Hif1-a pathway - Xiang-Dong Liu; Jian Zheng; Shuang Song; Zi-Jun Chen; Yu-Xi Wang; Si-Jia Zhang; Guan-Hua Zhang; Qun Lu; Ying-Liang Song (Adipocyte, 2023)
ABSTRACTCritical-size defects (CSDs) are challenging oral clinical issues that need to be solved. Adipose-derived mesenchymal stem cells (ADSCs) and gene therapy offer a new target to solve these issues. Consequently, ADSCs attract more and more attention because of advantages such as easy obtainability and no ethical concerns. TNF receptor-associated factor 6 (TRAF6) is a significant binding protein both of tumour necrosis factor superfamily and of the toll/interleukin-1 receptor superfamily. Evidence is accumulating that TRAF6 inhibited osteoclast formation and promoted the proliferation of multiple myeloma cell lines and bone resorption. Here, we reported that overexpression of TRAF6 enhanced the proliferation, migration and osteogenesis of ADSCs through Raf-Erk-Merk-Hif1a pathway. Cell sheet of ADSCs combined with TRAF6 accelerated the healing of CSDs. In a word, TRAF6 enhanced osteogenesis, migration and proliferation through Raf-Erk-Merk-Hif1a pathway.